An evaluation of the knowledge of patiens of the need to follow suitable lifestyles after hart surgery - Narloch, Agnieszka; Mędrzycka-Dąbrowska, Wioletta (Polish Journal of Public Health, 2015)
Introduction. Cardiovascular diseases are the leading cause of premature death in Europe. In Poland, the percentage mortality is 2,5 times higher than in Western European countries. Aim. To assess patients’ knowledge of the need for diet and physical activity after cardiac surgery. Material and methods. The study involved a group of 150 patients after cardiac surgery. The research was conducted at the Department of Cardiac and Vascular Surgery, University Clinical Centre in Gdansk. The study used a questionnaire of our own design. Results. Over half of the respondents stated that they had an average amount of knowledge with regard to healthy eating, while one in four had a less than average level of knowledge, and 16% opined that they had a superior knowledge of the same. These results are dependent on age and degree of formal education, and to adherence to dietary recommendations of gender, to financial situation and marital status. With regard to average dietary adherence, more women than men properly identified products harmful to human health. These last results bore little correlation to place of residence or degree of formal education. In addition, slightly more than half of the respondents (55.3%) practiced some sort of physical activity, but up 44.7% does not do any. More active were women and younger people (of both sexes), and those with higher degrees of formal education. Conclusions. Knowledge of patients with regard to diet after cardiac surgery is dependent on age and degree of formal education, and to adherence to dietary recommendations of gender, to financial situation and marital status. However, formal education and place of residence does not have a significant impact on the level of knowledge of products that are harmful to human health and behavior. Both sex, place of residence and degree of formal education have an impact on level of physical activity in general, as well as on its individual manifestations. More active are women, younger people and those with higher formal education.